Automatická tvorba animovaného videa na základě textového příběhu - Rosecký, Richard (Vysoké učení technické v Brně. Fakulta informačních technologií, 2025)
Cílem teoretické části této práce je popsat současný stav modelů generujících video, a to jak jejich architektury, tak konkrétní modely. V práci bude zhodnocena jejich kvalita, ne- dostatky a potenciální využití. Dále je v praktické části této práce cílem navrhnout a im- plementovat vlastní systém, který vylepší konzistenci subjektů v generovaných videích.

The goal of the theoretical part of this thesis is to describe and present the current state of video generative models with focus on used architectures as well as specific models currently on the market. The thesis will present their quality, shortcomings and potential usage. The goal of the practical part of this thesis is to design and implement a system which will enhance the subject consistency in generated videos.
Automatic Creation of Animated Video based on Textual Story
Keywords: modely generace videa; konzistence generovaných videí; difůzní modely; konzistence sub- jektů ve videu; hodnocení kvality videa; latentní difúzní modely; modul pozornosti; video generation models; consistency of generated videos; diffusion models; subject consis- tency in video; rating of video quality; latent diffusion models; attention module